UMAOH calcium phosphate coatings designed for drug delivery: vancomycin, 5-fluorouracil, interferon α-2b case - Prosolov, Konstantin A.; Komarova, Ekaterina G.; Kazantseva, Ekaterina A.; Lozhkomoev, Aleksandr S.; Kazantsev, Sergey O.; Bakina, Olga V.; Mishina, Marina V.; Zima, Anastasia P.; Krivoshchekov, Sergey V.; Khlusov, Igor A.; Sharkeev, Yuriy P. 1950- (Materials)
Drug delivery systems based on calcium phosphate (CaP) coatings have been recently recognized as beneficial drug delivery systems in complex cases of bone diseases for admission of drugs in the localized area, simultaneously inducing osteoinduction because of the bioavailable Ca and P ions. However, micro-arc oxidation (MAO) deposition of CaP does not allow for the formation of a coating with sufficient interconnected porosity for drug delivery purposes. Here, we report on the method to deposit CaP-based coatings using a new hybrid ultrasound-assisted MAO (UMAOH) method for deposition of coatings for drug delivery that could carry various types of drugs, such as cytostatic, antibacterial, or immunomodulatory compositions. Application of UMAOH resulted in coatings with an Ra roughness equal to 3.5 mu m, a thickness of 50-55 mu m, and a combination of high values of internal and surface porosity, 39 and 28%, respectively. The coating is represented by the monetite phase that is distributed in the matrix of amorphous CaP. Optimal conditions of coating deposition have been determined and used for drug delivery by impregnation with Vancomycin, 5-Fluorouracil, and Interferon-alpha-2b. Cytotoxicity and antimicrobial activity of the manufactured drug-carrying coatings have been studied using the three different cell lines and methicillin-resistant S. aureus.